PREOPERATIVE ANEMIA AS A PREDICTOR OF RECURRENCE IN GASTRIC CANCER - Pereira, Hugo; Viegas, Victor; Tavares, Carolina; Rocha, Alexandra; Amado, Andreia; Tavares, Amélia; Viveiros, Fernando; Vale, Sílvio; Pereira, Bela (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2025)
Introduction: Cancer-related preoperative anemia is one of the most common comorbidities in several malignancies. It has been reported as an independent prognostic factor for disease-free survival. The aim of this study is to investigate preoperative anemia as a predictor of recurrence in patients with gastric carcinoma. Methods: This is a retrospective study that included patients submitted to curative resection for gastric adenocarcinoma between January 2015 and December 2019 at our institution. We collected clinicopathological characteristics and chose a hemoglobin cut-off value (12.0 g/dL). Groups (anemia versus no anemia) were compared regarding disease-free survival (DFS) and overall survival (OS) using Kaplan-Meier curves and the log-rank test. Statistical analysis was performed using the SPSS program, with significance defined as p<0.05. Results: A total of 81 patients were included, with preoperative anemia defined as a hemoglobin level below 12.0 g/dL. The analysis revealed that anemia was significantly associated with decreased disease-free survival (DFS), with patients exhibiting a median DFS of 62.1 months compared to 65.7 months in non-anemic patients (p=0.040). Furthermore, anemia was linked to higher rates of lymphatic invasion (80.4% vs. 51.4%, p=0.008) and higher recurrence rates, especially distant recurrence (23.9% vs. 2.9%, p=0.010). Multivariate analysis confirmed that anemia remained an independent risk factor for recurrence (p=0.027), alongside lymphatic invasion (p=0.023). However, no significant impact on overall survival (OS) was observed. Discussion: The findings suggest that preoperative anemia serves as an independent marker of recurrence risk and highlights the importance of incorporating it into clinical decision-making. These results warrant further prospective, multicenter studies to confirm the role of preoperative anemia as a reliable prognostic factor in gastric cancer.